HOSPITAL IMPLEMENTATION OF THE PATIENT EXPERIENCE COMMITTEE - Guimarães, Lorena Freitas de França (2024)
The patient experience encompasses this set of aspects that aim to promote, in addition to the treatment of the disease, the quality of care, patient satisfaction and active involvement in care. This study has the general objective of describing how the process of implementing the Patient Experience program in our unit took place, as well as detailing the actions taken and the challenges faced in its implementation. Descriptive study of an observational nature, started in February 2022 and continued until June 2023, involving the observation of the admission, hospitalization and discharge steps of patients at the pediatric clinic at Hospital Geral Dr. Waldemar Alcântara, located in the city of Fortaleza-CE, carried out by members of the hospital's Patient Experience Committee. Adequacy of benches, changes in the patient admission and discharge flow, release of Wi-Fi internet network, release of toys, adjustment in companions' meals. This project was able to certainly impact the vivid experience of pediatric patients admitted to our institution, based on objective actions, with rearrangement of internal flows, optimization of resources, with low financial impact and at the same time, bringing a positive impact to our public.